ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MENERAPKAN CORPORATE SOCIAL RESPONBILITY PADA PT. BUKIT ASAM TBK - Butarbutar, Monetarist; Firmansyah, Putra (JURNAL NERACA AGUNG; Vol 10 No 1 (2020): MARET, 2020)
This study aims at determining whether there are differences in financial performance Profitability Ratios namely Return on Assets (ROA), Liquidity Ratios namely Current Ratio (CR), Solvency Ratios namely Debt Asset Ratio (DAR), Activity Ratios namely Total Asset Turn Over (TATO) and Market Ratio namely Earning Per Share (EPS) before and after implementing Corporate Social Responsibility (CSR) at PT. Bukit Asam, Tbk. In this study, five (5) financial ratios were used, namely Profitability, Liquidity, Solvency, Activity, and Market Value. In this study, the sampling method is the census method. The population in this study came from 14 financial statements from 2005 to 2018. Data collection methods used in this study are the library method and the field method. The test used in this study was a different T-test using Statistical Product and Service Solution (SPSS) version 21 for windows. The results in this study indicate that there are significant differences in the financial performance of ROA, CR, DAR and TATO before and after implementing CSR, but if it was viewed from the financial performance ratio that is EPS, there is no significant difference before and after implementing CSR